Effect of Bergamot and Laoxianghuang Polysaccharides on Gut Microbiota Derived from Patients with Hyperlipidemia: An Integrative Analysis of Microbiome and Metabolome during In Vitro Fermentation - Yang Zheng; Yi Wang; Donghui Luo; Lianzhu Lin; Xingyu Lu; Jie Gao; Chuqiao Xiao; Mouming Zhao (Foods, 2022)
The aim of this study was to investigate the effects of bergamot polysaccharide (BP) and Laoxianghuang polysaccharides (LPs, fermented bergamot) on the microbiome and metabolome during the in vitro fermentation of gut microbiota from patients with hyperlipidemia. Results indicated that both BP and LPs were able to increase the production of acetic acid, propionic acid, and butyric acid. However, only LPs could decrease the content of isobutyric acid and isovaleric acid, which are detrimental to gut health. A 16S rRNA analysis showed that both BP and LPs could reduce the proportion of Fusobacterium, whereas they increased the Bacteroides content in hyperlipidemia. Untargeted UPLC-MS/MS metabolomic profiling found six bio-markers that were significantly changed after BP and LPs intervention, and four of the down-regulated metabolites were long-chain fatty acids associated with vascular diseases. These findings provide new evidence that BP and LPs have the potential to regulate imbalances in the gut microbiota in patients with hyperlipidemia and ameliorate its metabolic abnormalities.